De novo complex X chromosome rearrangement unmasking maternally inherited CSF2RA deletion in a girl with pulmonary alveolar proteinosis. Issue 10 (5th August 2013) - Auger, Julie; Bonnet, Céline; Valduga, Mylène; Philippe, Christophe; Bertolo‐Houriez, Emmanuelle; Beri‐Dexheimer, Mylène; Schweitzer, Cyril; Leheup, Bruno; Jonveaux, Philippe
Abstract We report on a 3‐year‐old girl with a de novo complex X chromosome rearrangement associated with congenital pulmonary alveolar proteinosis (PAP) and short stature. Array comparative genome hybridization and FISH analyses contributed to characterize the complex rearrangement consisting of a 7.37 Mb terminal deletion of Xp22.33p22.2, a 17.3 Mb interstitial inverted duplication of Xp22.2p21.3, and a 10.14 Mb duplication of Xq27.3q28. PCR analysis of microsatellite markers supported a paternal origin of the X chromosome rearrangement. A pre‐meiotic two‐step mechanism may explain the occurrence of this complex X rearrangement: an inverted duplication deletion event on Xp, and duplication of the Xq27.3qter region through a telomere capture event stabilizing the broken chromosome Xp end. The girl has also inherited from her healthy mother an X chromosome with a colony stimulating factor 2 receptor, alpha (CSF2RA) gene deletion. Consistent with the recessive mode of inheritance, the de novo paternal Xp22.33p22.2 deletion combined to the maternally inherited CSF2RA gene deletion led to homozygous deletion of CSF2RA and PAP diagnosis in the girl. The Xp deletion encompasses the pseudoautosomal region 1 (PAR1) which contains genes that escape X inactivation. Short stature homeobox (SHOX) haploinsufficiency explains growth retardation. Absence of other symptoms in relation to the X deletion/amplification is most probably due to skewed X inactivation. Finally, inherited deletions may unmask rare pathogenic genomic rearrangement and contribute to clinical phenotypes by a recessive mode of gene action. © 2013 Wiley Periodicals, Inc.